Analysis of The Implementation of The Concept of Higher Airspace Operations in Indonesia - Limbong, Marchel Jeriko Togu; Medianto, Rully; Edi, Prasetyo; Gunawan, Gunawan; Rahmawati, Fajar Khanif; Prattiwi, Elisabeth Anna (Institut Teknologi Dirgantara Adisutjipto, 2025)
The advancement of aviation technology and growing airspace demand have introduced the Higher Airspace Operation (HAO) concept, which manages airspace above FL550 (55,000 feet). Globally, regions like the United States and the European Union are developing regulatory and technological systems to integrate HAO into existing air traffic management. In contrast, Indonesia’s readiness remains limited due to the lack of specific regulations, infrastructure, and surveillance capabilities. This study assesses Indonesia’s preparedness to adopt HAO through a Systematic Literature Review (SLR) and expert interviews. Findings indicate the need for adaptive policies aligned with technological progress, improved communication, navigation, and surveillance systems, and comprehensive legal frameworks to support emerging airspace vehicles such as High-Altitude Platform Systems (HAPS), suborbital aircraft, and reentry vehicles. The research also proposes a dynamic, collaborative operational model suited to Indonesia’s unique geographical conditions and institutional environment.